TECHNOLOGICAL QUALITIES OF THE SUGAR-CANE, CANE AND RATOON PLANT, AS A RESULT OF THE APPLICATION OF SLAG AND LIMESTONE - PRADO, Renato de Mello (Scientia Agraria, 2001)
In the aim of evaluating the effect of slag on the technological qualities of sugar-cane, in comparison to limestone, a field experiment was conducted during the first two cuttings of sugar-cane (variety SP80-1842), during the agricultural years of 1998/99 and 1999/00), planted in Ituverava, northern region of São Paulo State, in red-yellow dystrophic latesoil. Treatments consisted of two corrective agents, calcitic limestone and slag, applied in three doses equivalent to CaCO3, aiming an increase of the base saturation to 50, 75 and 100%, in addition to the control without corrective agent. On the occasion of harvest of cane and the ratoon plant, of 12 and 24 months after planting, respectively, the techonological analyses (brix; pol; purity and fibre), calculation of the theoretically recoverable sugar (ATR) of the sugar-cane and the area, and correlation of the ATR per area with the culm production, were carried out. The results show that with regard neither the slag nor the limestone affected the technological qualities evaluated of the sugar-cane. However according to the regression studies, application of only slag resulted for the plant cane in a linear relationship between the two variables culm production and sugar yield per hectare. With regard to the ratoon, the sugar yield per hectare was 22% higher when slag was applied, in comparison to limestone.